Athletes' retirement from elite sport: A qualitative study of parents and partners' experiences. (January 2019) - Brown, Christopher J.; Webb, Thomas L.; Robinson, Mark A.; Cotgreave, Rick
Abstract: Objectives: Athletes' experiences of transition out of elite sport have been well documented. Less is known, however, about how the family members of athletes experience the process of transition. This study aimed to gain an in-depth understanding of parents and partners' experiences and the way that they managed and interpreted their role in the process of transition. Method: Individual semi-structured interviews were conducted with the parents and partners (two male and five female) of seven retired elite athletes from the UK. Data were analysed according to the principles of interpretative phenomenological analysis. Results: Parents and partners experienced their own transition as they navigated uncertainty and upheaval in their own lives when the athletes retired. Parents and partners had to renegotiate their identity as they adjusted to changing roles and dynamics in their close relationships. Providing support to the former athletes was complicated by parents and partners' own difficulties during transition and they often felt unsure about their role as a supporter. Parents and partners often experienced difficulties in their relationship with the athletes during their transition, but things improved as time went by. This was due to better communication and a willingness to share their feelings about their experiences. This helped parents and partners to gain a positive perspective on their transition and a sense that their relationship with the athletes had strengthened and grown. Conclusions: Transition is often a shared experience and the findings of the present study underline the value of exploring transition at the level of the family or partnership as well as the individual. Highlights: An interpretive phenomenological analysis of parents and partners' experiences of transition. Parents and partners experienced a range of powerful emotions during the initial stage of transition. Parents and partners experienced changes in their own lives that were often difficult to navigate. The process of providing support to athletes was complicated by parents and partners' own difficulties during transition. Mutual disclosure and sharing of emotions contributed to personal and relational growth.